Construção de cartilha digital para apoio à educação em saúde das doadoras de leite humano - Oliveira, Ana Zélia Pristo de Medeiros (2022)
Breastfeeding is a common action for all women who have undergone a gestational process and have had their children and is the main factor for child growth and development in early childhood. Many puerpery women produce milk in addition to what their babies need and, if saldable this milk can be given. This hand-dealist milk can be used in intensive care units, hospitalization units and feed children that their mothers cannot breastfeed for little or no milk production. The incentive to give milk should be performed by all health professionals involved in the gestational process, from prenatal care to the puerperal period. However, the reality experienced in health services does not seem to be compatible with the reach and promotion of benefits, and it is necessary to know and intervene on the multiple factors that determine this phenomenon, considered simultaneously as a biological and social act, impregnated with ideologies and market interests. In this context, it is important to think about ways that can facilitate and contribute to increase the uptake of human milk donation. In this scenario, health education has been shown to be the main causative factor of the adhering. Therefore, the present work aimed to build educational material to support the health education of human milk donors. This is a methodological study focused on the description of the process of elaboration of educational technology for learning the process of donation of breast milk to the human milk bank. During the pandemic, all care related to breastfeeding and human milk donation and also related to human milk processing were updated and all professionals were trained to act assertively with all changes and this whole process was challenging for all. During this process, a channel was made available via WhatsApp so that women could answer their doubts about human milk donation and breastfeeding. To carry out the present work, a survey of the most frequent doubts was carried out and then a booklet was constructed with the necessary answers obtained in official documents and scientific articles. Thus, the present study may contribute positively to the dissemination of knowledge about breastfeeding and the donation of human milk, thus resulting in the increase in their support.